(untitled) (World Bulletin of Social Sciences, 2025)
This article presents a scattered collection of materials’ physical-mechanical properties and their mixture harvest due to the process effect , mixing methods, and equipment choice to analyze the process impact on various materials between compatibility degree , separation cases, and one kind mixture to take opportunities to see the released information.